1983
DOI: 10.1128/aac.24.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA homologies among H incompatibility group plasmids by restriction enzyme digestion and Southern transfer hybridization

Abstract: Plasmids belonging to the three HI plasmid incompatibility subgroups were characterized by the use of restriction enzymes and Southern transfer hybridization. A diversity of restriction enzyme patterns was noted among the HI subgroups, and a small amount of DNA homology was observed by probing these digests with a nick-translated HI1 plasmid. Within a single subgroup (HI1 and HI2), similar restriction enzyme patterns were noted. Plasmids of all three HI subgroups and the HII group had a guanine plus cytosine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…On the basis of DNA-DNA hybridization studies, the IncHI group of plasmids is further divided into three subgroups, IncHIl, IncHI2, and IncHI3 (42). Subgroups IncHIl and IncHI2 both have many plasmids, but there is only one plasmid, MIP233, in the IncHI3 subgroup (27).…”
mentioning
confidence: 99%
“…On the basis of DNA-DNA hybridization studies, the IncHI group of plasmids is further divided into three subgroups, IncHIl, IncHI2, and IncHI3 (42). Subgroups IncHIl and IncHI2 both have many plasmids, but there is only one plasmid, MIP233, in the IncHI3 subgroup (27).…”
mentioning
confidence: 99%
“…However, the exchange of DNA within plasmids, both by acquisition and loss of transposons, and by gene mutation and deletions (24) results in plasmids of the same incompatibility group having diverse total DNA. Various studies have demonstrated DNA variability within incompatibility groups by restriction endonuclease digests and DNA hybridization (25)(26)(27)(28). While plasmid incompatibility provides evidence for a common origin, a high degree of DNA homology demonstrated by identical or similar digest patterns is a useful indicator of current identity.…”
Section: Discussionmentioning
confidence: 99%
“…8). (42). The htdA determinant is shown in this study to encode a protein which is involved in the regulation of conjugative transfer of these plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, IncHII plasmids are nonthermosensitive for conjugative transfer but are constitutive for pilus synthesis (8). The IncHI group is further subdivided into subgroups IncHIl, IncHI2, and IncHI3 (26,42). This subdivision is based mainly on DNA homology studies, but the IncHI2 subgroup also encodes several characteristics, not found on IncHIl plasmids, such as resistance to potassium tellurite and inhibition of certain types of DNA phages (31,36).…”
mentioning
confidence: 99%